Imaging spectrum of renal masses on multi-slice computed tomography - Thakor, Dipak R.; Rana, Yashpal R.; Sheth, Megha M. (International Journal of Research in Medical Sciences, 2020)
Background: Multi-slice computed tomography (MSCT) is the mainstay for preoperative assessment of many complex renal masses in current clinical practice. Benign renal processes may simulate malignant renal tumors and could be defined correctly by CT. MSCT has also an important role in tumor staging. The purpose of this article is to understand the imaging spectrum of renal masses on MSCT and assess the usefulness of CT in surgical planning and management. Methods: Studied 500 patients with suspected renal lesions who underwent MSCT during the period July 2017 to July 2020 at state-of-art imaging center. CT imaging was done in those patients in whom clinical examination and ultrasonography (USG) revealed possibility of diagnosis of renal masses for further detailed evaluation and deciding management. Results: Out of 500 total subjects, the common age group in this study is 51 to 60 years (25%). Male preponderance (59%) was noted. The most common presentation was pain (84%) followed by lump (29.4%) and haematuria (17.8%). Malignant masses (51%) were more common followed by benign (39%) and inflammatory masses (10%) respectively. Renal cell carcinoma has more incidence (30%) followed by simple cyst (20%). Calcification (19.6%), perinephric extension (78%) and vascular invasion (21.5%) are more common in malignant masses. Conclusion: MSCT is the modality of choice for the diagnosis of renal masses and deciding management approach in current practice. Detection of tumoral spread, invasion of surrounding organs and vascular structure are better with CT. MSCT also has a role in postoperative follow-up of renal masses.